PENGARUH PROBLEM BASED LEARNING DAN KEMAMPUAN BERPIKIR KRITIS TERHADAP HASIL BELAJAR MAHASISWA - Wulandari, Nadiah; -, Sjarkawi; M, Damris (Program Magister Teknologi Pendidikan Universitas Jambi, 2011)
The present study investigates the effect of problem-based learning (PBL) and critical thinking skill variables on students’ achievements. The independent variables are PBL design instructional and the expository and discussion learning design instructional. The moderator variable is the level of critical thinking skills which was measured by the adaptation test from Cornell Test, California Critical Thinking Test, and Ennis Weir Essay Test. The experiment uses 2 x 2 factorial design with pretest and posttest. Participants are the students majoring in Industrial Engineering. The study was done in two groups: the PBL group and the Conventional group with 30 students of each of the group. Two Way ANOVA and Tukey Test are applied in the data analysis. The study revealed that there was a significant difference between the experiment and the control group on students’ achievements. The similar results also found on students with high critical thinking skills. There was also an interaction between teaching approach and critical thinking skills in effecting students’ achievement. Keywords: problem based learning, critical thinking skills, cognitive result of learning, and affective assessment